Secular trends of vitamin D and calcium intake and their circulating levels in US adults from 2007 to 2018 - Du, Yongliang; Ma, Chao; Shang, Zhaoyue; Zhang, Xiaohua; Duan, Yanlin; Liu, Tong; Yu, Yang; Yang, Shuman (Frontiers in Nutrition, 2025)
BackgroundFew studies have examined the secular trends of total calcium and vitamin D intake and their circulating levels together among adults in the United States (US). Understanding the trends of these nutrients may be useful for refining existing nutrition policy and guidelines.ObjectiveThe aim of this study was to report trends in total calcium and vitamin D intake and their circulating levels in the US population aged 18 years or older in 2007–2018.MethodsThis cross-sectional study identified adults aged 18 years or older in the US National Health and Nutrition Examination Survey (NHANES) from 2007 to 2018. Calcium and vitamin D intake including their supplements were the average of two 24-h recalls. Serum calcium and serum 25-hydroxyvitamin D [25(OH)D] were measured using established methods. Weighted regression was used to test trends in calcium and vitamin D intake, and serum total calcium and 25(OH)D levels.ResultsThis research included 16,751 participants, including 9,046 males and 7,705 females. Serum total calcium significantly decreased with survey years from 2007 to 2018 (9.42 to 9.31 mg/dL) (P trend <0.001). Calcium intake declined from 2009 to 2018 (1,070 to 1,010 mg/day; P trend <0.001). In contrast, vitamin D intake and serum 25(OH)D increased with survey years (5.8 to 11.0 mcg/day and 65.6 to 68.5 nmol/L, respectively; all P trend <0.001). The trends in calcium intake vs. serum total calcium (P trend interaction =0.267), and vitamin D intake vs. serum 25(OH)D with survey years were comparable (P trend interaction =0.190). Inadequate vitamin D intake decreased with survey years (86.0 to 80.2%; P trend = 0.002). Moderate vitamin D deficiency (22.3 to 21.5%; P trend = 0.043), but not severe vitamin D deficiency (3.3 to 2.9%; P trend = 0.119), also declined with calendar years.ConclusionFrom 2007 to 2018, US adults showed a decrease in serum total calcium, and an increase in serum 25(OH)D levels. Both trends were partly due to declined calcium and increased vitamin D intake.